A SPECTROSCOPIC IN-VITRO METHOD FOR DETERMINING THE SUN PRODUCTION FACTOR (SPF)AND PHYSICAL PROPERTIES OF MARKETED SUNSCREEN FORMULATIONS - Ahmed Hassan kurda (Science Journal of University of Zakho)
Applying sunscreen or lotion protects the skin from harmful ultraviolet rays, reducing the risk of sun exposure-related diseases such as skin cancer. The increasing awareness of these dangers has driven a demand for testing sunscreen formulations. This research utilizes ultraviolet-visible spectroscopy to measure the Sun Protection Factor (SPF) and the UVA/UVB ratio for several different sunscreens from various brands. The SPF values of the tested products range from 15 to 100. The spectroscopy method is simple, fast, and accurate in determining SPF values in a controlled environment. Notably, some sunscreen formulations in the Kurdistan market display SPF values 62.5% below the label amount, indicating that many people in Kurdistan may be using sunscreens with less protection than they believe. Besides evaluating SPF, the research also examines the tested sunscreens' optical band gap and refractive index.